2023
DOI: 10.1109/access.2023.3298107
|View full text |Cite
|
Sign up to set email alerts
|

Forward Scatter Shadow Ratio: Concept and Its Application in Shadow Profile Retrieval

Abstract: Traditionally, the radar cross-section is used to characterize the target in a forward scatter radar (FSR) system, the measurement of which requires the availability of the scattered signal. However, the scattered signal is often hard to be extracted, particularly when the illumination signal is opportunistic. In this paper, we introduce the concept of the forward scatter shadow ratio (FSSR) of a target as the ratio of the total received power density to the incident power density for a receiver at a certain l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The physics behind radar systems encompasses two primary types of scattering: forward scattering and backscattering [42,77]. Forward scattering is detailed through a modern perspective, indicating that radar waves can scatter in the direction forward from their original path when the bistatic angle, the angle from the transmitter, through the target, to the receiver, is close to 180 β€’ [84][85][86][87]. This scattering is particularly advantageous for detecting small or RF-absorbent targets, such as small drones, due to the enhanced RCS in such conditions.…”
Section: Radar Scatteringmentioning
confidence: 99%
“…The physics behind radar systems encompasses two primary types of scattering: forward scattering and backscattering [42,77]. Forward scattering is detailed through a modern perspective, indicating that radar waves can scatter in the direction forward from their original path when the bistatic angle, the angle from the transmitter, through the target, to the receiver, is close to 180 β€’ [84][85][86][87]. This scattering is particularly advantageous for detecting small or RF-absorbent targets, such as small drones, due to the enhanced RCS in such conditions.…”
Section: Radar Scatteringmentioning
confidence: 99%
“…1) is also established, with axes π‘₯β€², 𝑦′ and 𝑧′ parallel with axes π‘₯, 𝑦 and 𝑧, respectively. As in [6,7], the target is considered moving straight in the 𝑧 1 Systems in a spherical wave can be converted to plane wave equivalent systems [6]. direction on the π‘₯-z plane, i.e., the origin of the π‘₯ βˆ’ 𝑦 βˆ’ 𝑧′ system is moving straight in the 𝑧 direction on the π‘₯ βˆ’ 𝑧 plane.…”
Section: A the Fssr Modelmentioning
confidence: 99%
“…Forward scatter shadow ratio (FSSR), defined as the ratio of the total received power density to the direct path signal (DPS) power density, is a parameter to describe the target in an FSR system [6][7][8]. Compared with forward scatter cross section (FSCS) [9,10], it has been shown that FSSR is more relevant to passive FSR systems [6][7][8]. Based on FSSR, an optimization method for target shadow profile retrieval has been recently proposed [7,8,11,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a new parameter to describe the target in the forward scatter radar (FSR) system with a plane wave as the signal source, namely the forward scatter shadow ratio (FSSR), was introduced [1][2][3]. As a parameter relevant to target detection, size estimation, classification and shadow profile imaging, FSSR is defined as the ratio of the total received power density to the direct path signal (DPS) power density.…”
mentioning
confidence: 99%